A parent‐completed respiratory questionnaire for 1‐year‐old children: repeatability - Strippoli, Marie‐Pierre F (BMJ Group, 2007)
BACKGROUND AND AIMS: There are few standardised questionnaires for the assessment of respiratory symptoms in preschool children. We have developed and tested the short‐term repeatability of a postal questionnaire on respiratory symptoms for 1‐year‐old children. METHODS: A newly developed postal questionnaire for the assessment of wheeze and other respiratory symptoms was sent to parents of a population‐based random sample of 4300 children aged 12–24 months. After an interval of 3 months, a random sample of 800 respondents received the questionnaire a second time. The responses were compared using Cohen's kappa (κ) to assess agreement corrected for chance. RESULTS: The first questionnaire was returned by 3194 (74%) families, the second one by 460/800 (58%). Repeatability was excellent (κ 0.80–0.96) for questions on household characteristics, environmental exposures and family history, good (κ 0.61–0.80) for questions on prevalence, severity and treatment of wheeze, and moderate (κ 0.39–0.66) for chronic cough and upper respiratory symptoms. CONCLUSIONS: This short postal questionnaire designed for use in population‐based studies has excellent repeatability for family and household characteristics and good repeatability for questions on wheeze. Short‐term changes in symptom status might be responsible for variable answers on recent chronic cough and upper respiratory symptoms. Overall, the questionnaire is a valuable instrument for community‐based research on respiratory symptoms in 1 to 2‐year‐old children.